Risks of infection with the HIV: Sociological assessment - I. B. Nazarova; R. S. Nesterov (RUDN journal of Sociology)
The human immunodeficiency virus (HIV) is a complex socially significant disease associated with risks mainly for representatives of groups practicing deviant behavior and requiring special attention from the state and society. The article presents a comprehensive description of representatives of the high-risk group for the HIV infection, including their health status, behavioral characteristics, types, combinations and perceptions of risks, which would allow for a more optimal organization of the work of social and medical services with this group. The article is based on the results of the empirical study conducted in 2022: 3,792 clients of the charitable foundation “Support for Social Initiatives and Public Health” were questioned within the HIV preventive work with representatives of high-risk groups. A significant part of clients are people under 22 years of age (25 %). Their main risks were divided into condition risks and behavioral risks. Condition risks are as follows: current and past illness (29 % were diagnosed with an infection or several ones, including the HIV), unemployment (21 %), difficult financial situation (9 %); and for foreign citizens also lack of citizenship (24 %) and not speaking Russian (5 %). Behavioral risks (actions leading to loss of health or inaction in health protection) are as follows: 15 % of clients use drugs (including with shared equipment for injecting), the majority (76 %) consciously agree to unprotected sex and have multiple sexual partners (the average number is 21 per year). In general, representatives of high-risk groups tend to underestimate their risks, and awareness is not a decisive positive factor, i.e., it does not necessarily change behavior to less risky. Moreover, long-term risk practices together with knowledge of risks and protective measures can negatively affect perceptions of risks; thus, clients with experience of risk behavior consider risks as less dangerous or deny risks in principle, which is an additional risk for both the person and one’s partners.